(3GdOQI GdHgjI aj HjGf HYV haGI hhdGOI Ch GMOgeG ef YdeGA CUMGH GdELGRI hTjhNfG ef HYO GdKdGKeGFI gLQjI Edi GdBfs - (3GdThjcj, GdHMQGfj, eQRhb Hf eMeO Hf YHO Gddg, J b (B13 (3g`s ((3LHd GdCFeI GdGKfj YTQ (B( (3LHd QVhi (B)s)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj ehQO aj gPg GdQSGdI (B... (3HjGf HJGQjN HYV ef hdO Ch eGJ ef YdeGFfG GdeJeScjf HLHd GdCFeI GdEKfi YTQjI eef hbaJ Ydi JGQjN dg aj CjYGe hdO Ch eGJ ef GdCYhGe GdcGFfI ef gLQI eMeO NjQ GdHQjI (B...s
(3BNQgG (B:s
... (3hdbO cGf YGdeG aGVdG eJcdeG eGJ aj GdYGe GdJj eGJ ajg GNhI GdTjN YHO Ydj EdG Gfg HTgQ QLH hPdc HPj GdbYOI hKGdKge GdYGde GdChMO GdTjN CMeO MQSg Gddg GdCMO cGf YGdeG aGVdG (B.. (3hLQi Pdc hMQQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\842s
(3GdPQjYI (B26 \ 1479s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs